Isolation and immunophenotypic characterization of mesenchymal stem cells derived from equine species adipose tissue - Carvalho, Armando de Mattos [UNESP]; Alves, Ana Liz Garcia [UNESP]; Golim, Marjorie de Assis [UNESP]; Moroz, Andrei [UNESP]; Hussni, Carlos Alberto [UNESP]; Gomes de Oliveira, Patricia Galvao [UNESP]; Deffune, Elenice [UNESP] (Elsevier B.V., 2009)
The purpose of this work was to isolate and cultivate mesenchymal stem cells (MSC) derived from equine adipose tissue and conduct cellular characterization with the following markers: CD90, CD44 and CD13. Adipose tissue collection was performed at the base of the horses' tails, followed by immediate isolation and cultivation of the MSC and posterior characterization by flow cytometry for the interspecies reaction test using mouse anti-rat CD90 monoclonal antibody (mAb), fluorescein isothiocyanate (FITC), and tests with specific mAb mouse anti-horse CD13 and mouse anti-horse CD44. The technique used for isolation and cell cultivation proved to be safe and viable. The CD90 mAb expressed cross-reaction with MSC derived from equine adipose tissue and CD44 showed greater expression in cells as the number of culture passages increased. Although marker CD13 expresses reaction in other studies involving MSC in different species, it presented no expression in the experiment realized. The results obtained revealed the immunophenotypic characterization of the surface of isolated and cultivated MSC, classifying these cells as a promising type of progenitor cells that can be applied in equine cellular therapy. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Immunophenotypic characterization; Equine; Adipose tissue; Mesenchymal stem cells